Improving Body Mass Index in Students with Excess Weight through a Physical Activity Programme - Scurt Mădălina Doinita; Balint Lorand; Mijaica Raluca (My University, 2022)
The obesity epidemic among young people can be tackled through regular physical activity. For this purpose, we developed and implemented a physical activity programme (PAP) that we carried out in students’ free time during the school year 2018–2019. The target group consisted of 79 students with excess weight, aged between 12 and 15 years, selected from an initial sample of 495 students from 5 pre-university education units located in an urban area. That group followed a differentiated PAP for 26 weeks. The impact of the programme highlighted the following points: the average physical activity/week for the entire sample of subjects was 3.67 physical activities, with an allocated time/week ranging from 1 h 30 min to 3 h; in terms of effort intensity, 7.70% of the activities were performed at low intensity, 75.07% at medium intensity and 17.23% at submaximal intensity. At the end of the programme, out of 79 subjects who were overweight/obese at the initial testing, 37 improved their body composition at the ﬁnal testing, with a healthy BMI. It was also found that there is a negative correlation coefﬁcient (r = −0.23) between the time spent performing physical activities and the BMI of the subjects.
Keywords: physical activity; programme; children and adolescents; excess weight; urban environment